Fibrin Affinity and Clearance of t-PA Deletion and Substitution Analogues - Johannessen, M; Diness, V; Pingel, K; Petersen, L C; Rao, D; Lioubin, P; O’Hara, P; Mulvihill, E (Thrombosis and Haemostasis, 1990)
To investigate structure-function relationships in tissue-type plasminogen activator (t-PA) we deleted the following domains in the heavy chain: a) The epidermal growth factor domain (t-PA del. G), b) the finger domain, and the epidermal growth factor domain (t-PA del. FG), and c) the finger, the epidermal growth factor and Kr-ingle 1 (1-PA del, FGK1). To study specificly the function of the growth factor domain we made two substitutions of d) 8 amino acids (consensus sequence) in the growth factor domain (t-PA G-CS) and c) the whole domain with factor IX growth factui doniuin (t-PA G-IX). Finally, f) an analogue with substitution in the finger domain (fibronectin consensus sequence) was constructed (t-PA F-CS).A reduced fibrin binding of all the analogues was found. The fibrin stimulated activity of all analogues was also reduced and correlated to the fibrin binding. In contrast, the activity of the analogues in the clot lysis assay and the plate assay were only slightly reduced as compared to authentic t-PA. This suggested that at high fibrin concentrations the decreased fibrin affinity was less ciitical for obtaining a high fibrinolytic activity.All analogues had a prolonged half-life in vivo as compared to authentic t-PA. The assumption of clearance mechanism involving mainly the growth factor region (or Kringlc 1) was not challenged by the observation of a prolonged half-life for the substitution analogue t-PA F-CS.Our results indicate that a high affinity for fibrin and rapid elimination in vivo of t-PA require a nearly intact conformation of the N-terminal part of the molecule.
Keywords: Tissue-type plasminogen activator; Deletion analogues; Substitution analogues; Fibrin binding; Clearance; Fibrin stimulation; Clot lysis activity